The Effects of Surgical Timing on Treatment Outcomes in Carpal Tunnel Syndrome - Fatih DURGUT; Erdem ŞAHİN; Mehmet Sait AKAR; Ali ÖZDEMİR; Şeyhmus YİĞİT (Bezmiâlem Science, 2022)

(untitled)
Objective:The purpose of this study is to assess and compare outcomes of two different timing surgery for moderately carpal tunnel syndrome (CTS).Methods:Eighty-eight patients who underwent early and late due to CTS were evaluated retrospectively. Patients with early surgery and late surgery were divided into two groups. Preoperative and postoperative visual analog scale (VAS) score and postoperative Boston Carpal Tunnel Questionnaire (BCTQ) scores of both groups were compared.Results:Preoperative and postoperative VAS scores were compared, there was a significant decrease in both groups. When BCTQ results of both groups were compared, the results of patients who underwent early surgery were statistically better.Conclusion:In conclusion, we think that early surgery is better clinically in patients with moderately CTS.